2018
DOI: 10.1159/000491911
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-374a Inhibits Aggressive Tumor Biological Behavior in Bladder Carcinoma by Suppressing Wnt/β-Catenin Signaling

Abstract: Background/Aims: microRNA (miR)-374a plays a crucial role in cancer progression by promoting the metastasis and proliferation of various types of malignant tumors. Because its role in bladder cancer is unknown, we investigated whether miR-374a affects the progression of bladder cancer and studied the underlying mechanism. Methods: The Cancer Genome Atlas was used to analyze the clinical relevance of miR-374a. Quantitative PCR, western blotting, and luciferase and immunofluorescence assays were used to detect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…More than 2,500 miRNAs have been validated in the human genome 10. Recently, miRNAs were found to be dysregulated in most human cancer types, such as lung cancer,11 colorectal cancer,12 breast cancer,13 and bladder cancer 14. Particularly, a variety of miRNAs are aberrantly expressed in cervical cancer 15.…”
Section: Introductionmentioning
confidence: 99%
“…More than 2,500 miRNAs have been validated in the human genome 10. Recently, miRNAs were found to be dysregulated in most human cancer types, such as lung cancer,11 colorectal cancer,12 breast cancer,13 and bladder cancer 14. Particularly, a variety of miRNAs are aberrantly expressed in cervical cancer 15.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also showed that in BC, direct targeting of WNT5A by miR-374a treatment inhibited the phosphorylation and nuclear translocation of β-catenin, thus decreasing the expression of BC stemness-related proteins and the aggressiveness behavior of BC [124]. Other miRNAs which inhibit bladder CSCs proliferation, self-renewal, and metastasis are miR-139-5p (by targeting the Bmi1 oncogene [125]), miR-379-5p (by targeting MDM2 [126]), miR-125a-5p (by targeting FUT4 [127]), and miR-24 (by targeting CARMA3 [128]), suggesting that miRNAs could become a novel small-molecule therapeutic target for urothelial carcinoma.…”
Section: Micrornas (Mirnas)mentioning
confidence: 97%
“…The particular miRNAs in this paper are associated with cancer occurrence, metastasis and invasion. Indeed, miR-145, miR-202 and miR-374 has been proposed as diagnostic, prognostic or therapeutic marker of BLCA [45,46] .miR-202 and miR-347 participate in invasion, metastasis and cancer progression [46,47], while miR-145 modulates suppressor of cytokine signaling 7 (socs7) to enhance IFN-β expression, thus contributing to BLCA apoptosis. We speculate that deregulation of these miRNAs would be in consistence with the phenotype of POLR2K overexpression in BLCA, which should be further veri ed by experiments.…”
Section: Discussionmentioning
confidence: 99%